The role of journalists covering conflicts in Kazakhstan - Mussa, М.Н.; Myssayeva, Қ.Н. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2024)
Research on the conflict in Kazakhstan spans many fields, including political science, sociology, and history. Many scholars and organizations contribute to the understanding of the causes, nature, and resolutions of conflicts in the country. This article examines how journalists in Kazakhstan disseminate information about the conflict within the framework of state restrictions and editorial requirements, and finds that media representatives face critical challenges such as ethical issues, self-censorship, government pressure, and difficulties in achieving objectivity and accuracy. A survey of journalistic community members conducted between August 1 and August 30, 2024 revealed that Kazakhstani journalists try to adhere to the basic principles of journalism, such as editorial standards and neutrality, honesty, and responsibility, despite resource constraints or various pressures during conflict events. However, it became clear that self-restraint (self-censorship) of journalists forces them to circumvent censorship and find a balance between editorial demands and personal moral principles. The study revealed that restraint and personal initiative are important tendencies for journalists writing about conflict. This study shows that media independence, journalistic experience and self-activity are important in covering conflicts. Framing theory was used to analyze and discuss the results.